Auswanderung und Identität: Erfahrungen von Exil, Flucht und Migration in der deutschsprachigen Literatur - Sandor, Gabriela; Kory, Beate Petra; Baltes-Löhr, Christel (transcript, 2019)
A view at migration and exile in German-language literature with a focus on memories and identity, theoretically framed by the character of continuum.